Analysis of data from three centers in Turkey on intraoperative radiotherapy of breast cancer - Yıldırım Altınok, Ayşe; Alan, O. Day; Dizdar, Nihal; Çağlar, Hale Başak; İnce, Ümit; Uras, Cihan; Bese, Nuran (Elsevier Science Ltd., 2016)
[Abstract Not Available]
10th European Breast Cancer Conference (EBCC) -- MAR 09-11, 2016 -- Amsterdam, NETHERLANDS
WOS: 000371779500138
Keywords: Breast Cancer; Intraoperative Radiotherapy; Turkey